Polygamy Permits for Business Reasons (Analysis of Sawahlunto Religious Court Ruling Number: 045/Pdt.G/2018/PA.SWL) - Zainal Azwar; Firdaus Firdaus; Anshari Az Zarqy (Institut Agama Islam Negeri Batusangkar, 2021)
Under Law number 1 of 1974 article 4 and article 57 compilation of Islamic law, polygamy can be permitted for several reasons (conditions); The wife does not carry out duties as a wife, there are bodily defects or diseases that cannot be cured, and cannot bear offspring. In contrast, the judge at the Sawahlunto Religious Court granted the polygamy permit application on business grounds. The questions that will be answered in this article are; First, what is the consideration of the Sawahlunto Religious Court judge granting the application for polygamy permit on business grounds? Second, what is the decision of the Sawahlunto Religious Court on polygamy permits on business grounds when viewed from the opinion of jurists? This research is categorized as a field research, used interview and documentation as the techniques in gathering the data. This paper concludes: first, the consideration in granting the application because there is a written permission given by the wives, the husbands are able to be fair, the permission brings prosperity and benefit to husbands wives and children beside building the houselod integrity and the future of their business. Second, the second Religion Court Decision number 045/Pdt.G/2018/Pa.Swl. The Fiqih Scholars open up the oppertinity of polygamy practice for other reasons that switch to the social context and needs, a fairness as the main requirement.